(untitled) (Publicaciones en Ciencias y Tecnología, 2015)
It is important to know the thermal barrier deposition techniques since materials with low thermal conductivity in the barrier can be obtained from them. The dependence of the thermal conductivity with the temperature can be divided into four regions. In this work, we were interested in the study of used techniques for the manufacture of materials with a desirable low thermal conductivity that will be exposed to high temperatures that is to say, materials found in the III and IV region. In these regions the thermal conductivity can be reduced increasing the porosity of the material. Through the study of the thermal barrier deposition techniques we found that the thermal spray produces a coat with high porosity, being the low velocity flame spray technique the best to produce coat of La2Zr2O7 with a minimal thermal conductivity. The thermal spray technique is low cost and almost any material can be thermally sprayed, so this can be considered a very attractive technique for industrial applications.